2016
DOI: 10.20944/preprints201609.0074.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Regulation of ERK and AKT Pathways by Hepatitis B Virus X Protein via Notch1 Pathway in Hepatocellular Carcinoma

Abstract: Abstract. Hepatitis B virus (HBV) is the dominant risk factor for hepatocellular carcinoma (HCC). HBV X protein (HBx) plays crucial roles in HCC carcinogenesis. HBx interferes with several signaling pathways including the Notch1 pathway in HCC. In this study, we found that Notch1 was highly expressed in HCC, especially in large HCCs. Notch1 and HBx co-localized in HCC and their levels were positively correlated with each other. Notch1 expression was more elevated in HepG2.2.15 cells than that in HepG2 cells. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…HBx-enhanced androgen receptor activity is suppressed by sorafenib via the activation of SHP-1 phosphatase, which antagonizes Akt/GSK3β and c-Src pathway activation via HBx [13]. HBx activates the Notch1 pathway, which inhibits dual-specificity phosphatase 1 (DUSP1) and PTEN expression, promoting HCC cell survival [14].…”
Section: Introductionmentioning
confidence: 99%
“…HBx-enhanced androgen receptor activity is suppressed by sorafenib via the activation of SHP-1 phosphatase, which antagonizes Akt/GSK3β and c-Src pathway activation via HBx [13]. HBx activates the Notch1 pathway, which inhibits dual-specificity phosphatase 1 (DUSP1) and PTEN expression, promoting HCC cell survival [14].…”
Section: Introductionmentioning
confidence: 99%
“…HBx, the main regulatory protein encoded by HBV, is not considered to be directly transforming but plays a significant positive role in HBVassociated hepatocarcinogenesis (10). HBx has been reported to support β-catenin activation, which is highly associated with HBV-positive HCC (26,36,37). However, transgenic mice expressing HBx in hepatocytes under control of the α-1-antitrypsin promoter (ATX mice) do not develop tumors at higher rates than wild-type controls (21), and we did not observe significant β-catenin activation in 12-month-old ATX mice without other intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of AKT by HBx protein downregulates HNF4α transcription in rat hepatocyte and suggested to contribute to the development of HBV-associated HCC [14,32]. In addition to AKT signaling pathway, HBx can regulate ERK through Notch1 pathway in HCC [14,20].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that the rat sarcoma virus (Ras)/Raf/MEK/ERK signaling pathway, c-Jun N-terminal kinase (JNK) pathway and phosphoinositide 3-kinase (PI3K)/AKT signaling pathway are the major signaling pathways regulating cell proliferation and differentiation in HCC cells [17,18]. Among these, ERK signaling pathway is one of the main pathways in HCC which is associated with cell proliferation [19], and previous studies have revealed that HBx activates ERK signaling pathway [20][21][22].…”
Section: Introductionmentioning
confidence: 99%